2016
DOI: 10.2188/jea.je20150252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individual, Spousal, and Offspring Socioeconomic Status on Mortality Among Elderly People in China

Abstract: BackgroundThe relationship between socio-economic status and health among elderly people has been well studied, but less is known about how spousal or offspring’s education affects mortality, especially in non-Western countries. We investigated these associations using a large sample of Chinese elderly.MethodsThe data came from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) from the years 2005 to 2011 (n = 15 355, aged 65–105 years at baseline; 5046 died in 2008, and 2224 died in 2011). Educational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 34 publications
6
42
0
Order By: Relevance
“…The negative association between the share of children who attended college and the timing of parents’ death appears to be robust to the inclusion of children’s transfers and financial status, which are likely mediators in the case of Mexico. These findings broadly support previous studies, citing the advantages of children’s higher education for parental longevity (Friedman and Mare, 2014; Sabater and Graham, 2016; Torssander, 2013; Yang et al, 2016; Zimmer et al, 2007). Indeed, the results underscore how offspring education may matter most for older parents at the most extreme end of the health continuum.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The negative association between the share of children who attended college and the timing of parents’ death appears to be robust to the inclusion of children’s transfers and financial status, which are likely mediators in the case of Mexico. These findings broadly support previous studies, citing the advantages of children’s higher education for parental longevity (Friedman and Mare, 2014; Sabater and Graham, 2016; Torssander, 2013; Yang et al, 2016; Zimmer et al, 2007). Indeed, the results underscore how offspring education may matter most for older parents at the most extreme end of the health continuum.…”
Section: Discussionsupporting
confidence: 90%
“…Despite these supports, the Taiwanese studies show that schooling of the most well-educated child is negatively correlated with the severity of parents’ functional limitations (Zimmer et al, 2002) and positively associated with parental longevity (Zimmer et al, 2007). A more recent study from China found similar results, where the education of co-resident children is positively associated with parental longevity (Yang et al, 2016). Even in contexts where norms of intergenerational obligation are not as strong and older adults often rely on non-familial resources to maintain their well-being, having better-educated children also delays parents’ mortality.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…The CLHLS is a community-based longitudinal cohort with the aim of examining factors that promote longevity and quality of life among the older adults. However, we have noticed that the CLHLS study has been limited principally to social science research,3–18 whereas other objective medical aspects such as biomarkers are not available. As a result, such a major obstacle has been preventing us from developing a complete understanding of the determinants of healthy aging.…”
Section: Introductionmentioning
confidence: 99%